Jahrbuch der berufs- und wirtschaftspädagogischen Forschung 2018. - Wittman, Eveline; Frommberger, Dietmar; Ziegler, Birgit (Schriftenreihe der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2018)
Das Jahrbuch für Berufs- und Wirtschaftspädagogik gibt einen Überblick über den aktuellen Stand der einschlägigen Forschung. Mit diesem Zuschnitt wird dem breiten thematischen und methodologischen Spektrum der Forschung und Theoriebildung in der Berufs- und Wirtschaftspädagogik Rechnung getragen.; The Jahrbuch für Berufs- und Wirtschaftspädagogik provides an overview of the current state of relevant research. This volume takes into account the broad thematic and methodological spectrum of research and theory formation in vocational and business education.; What are the goals and conditions for the success of computer education in elementary and primary education? With a view to the pedagogical and content-related target dimensions of informatics education, experts in the field make recommendations for the development of the content offerings of the "House of Little Researchers" Foundation in the field of informatics. In addition, the implementation of these recommendations is illustrated in the Foundation's offerings.